Wallenberg’s Syndrome in Young Adults: Case Report - Thapa, Dinesh K; Yadav, Chandra Prakash; Limbu, Chandra Prakash; Dhakal, Sudan (Birat Journal of Health Sciences, 2018)
Wallenberg’s syndrome which is also known as Lateral medullary syndrome and posterior inferior cerebellar artery syndrome is a very rare cause of cerebrovascular accident (CVA). This has variability of presentation which cause the under diagnose for Wallenberg Syndrome. Generally ischemic CVA and especially medullary infarction occurs in the old patients but here we report two cases of Wallenberg syndrome in young adults, first is 35 years male and second is 38 years female. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 306-308